The nexus of IoT and aquaculture: A bibliometric analysis - Abderahman Rejeb; Karim Rejeb; John G. Keogh (Applied Food Research)
The Internet of Things (IoT) in aquaculture presents significant opportunities for improving the sector's productivity, sustainability, and resilience. This study aims to achieve two primary goals: to deliver an extensive overview of IoT applications in aquaculture and to pinpoint emerging trends and research gaps, thereby directing future academic endeavors in the aquaculture field. Through bibliometric analysis, which involved keyword co-occurrence and article co-citation network analyses, we investigated 428 publications from 2012 to 2024 retrieved from Scopus. The review indicates a significant rise in investigative efforts, especially in recent years, highlighting the sector's increasing focus on the role of IoT in tackling the distinct challenges aquaculture faces, including water quality monitoring, disease prevention, and resource efficiency. Prominent themes recognized encompass advanced aquaculture systems, water quality and health monitoring, and sophisticated forecasting tools. This investigation enhances the existing knowledge base by emphasizing key themes, significant studies, and essential technological advancements in IoT-enabled aquaculture, providing one of the initial bibliometric assessments in this swiftly developing field. Future research should focus on enhancing interoperability among IoT devices, improving data security and privacy, integrating artificial intelligence for predictive analytics, and expanding IoT applications to support small-scale and resource-constrained aquaculture operations.